Phyllodes tumor presented as fungating mass on right breast and fibroadenoma on contralateral breast: a case report - Mahapatra, Sribatsa Kumar; Panigrahi, Pramit Ballav; Mahapatra, Abinash; Mahapatra, Srimanta (International Surgery Journal, 2020)
This is an article reporting a large phyllodes tumor with fibroadenoma. A 25 years female presented with a fungating mass of size 20×15 cms in right breast since last 1 year and amass of size 3×3 cms in left breast since 6 month. Biopsy from right side and left side breast mass proven to be Cystosarcomaphyllodes and fibroadenoma respectively. Wide local excision with 1cm normal tumor margin on right side and excision of mass on left side done. Proliferative markers like Ki-67 and P53 were in range of 1-2% and 3-4% respectively. Histopathological diagnosis of tumor was borderline phyllodes tumor (right side) and fibroadenoma (left side). Patient had an uneventful post-operative course and is presently on three monthly follow up since 1 year.